2019
DOI: 10.1002/jgc4.1149
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genetic counseling on patient engagement in a specialty cancer clinic

Abstract: The identification of patient outcomes unique to the field of genetic counseling has become a recent priority of the profession. Current health-care efforts have targeted patient engagement as an outcome capable of improving population health and reducing health-care costs. This study analyzed patient engagement levels among 182 participants who underwent genetic counseling for gastrointestinal (GI) cancer risk assessment in an outpatient specialty clinic. Patients seen at the UPMC Hereditary GI Tumor Program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Studies of genetic counseling service delivery in numerous specialties have demonstrated the clinical and economic value of genetic counselor involvement on the health care team. Improvements in adherence to clinical management recommendations, 19 appropriate test selection, 20 mitigation of errors in genetic test ordering and interpretation, 21 increased patient engagement, 22 and more positive perceptions of the genetic diagnostic process 23 have been reported. Our data suggests that involvement of a genetic counselor in the CFNBS diagnostic resolution process is associated with higher rates of CFTR phasing.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of genetic counseling service delivery in numerous specialties have demonstrated the clinical and economic value of genetic counselor involvement on the health care team. Improvements in adherence to clinical management recommendations, 19 appropriate test selection, 20 mitigation of errors in genetic test ordering and interpretation, 21 increased patient engagement, 22 and more positive perceptions of the genetic diagnostic process 23 have been reported. Our data suggests that involvement of a genetic counselor in the CFNBS diagnostic resolution process is associated with higher rates of CFTR phasing.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, change in empowerment was not associated with clinical and demographic patient characteristics assessed in our cohort. Empowerment has been embraced as a critical outcome in GC practice as patient engagement and empowerment have been shown to increase medical adherence and to help facilitate health behaviors (Rutherford et al., 2014; Zakas et al., 2019). Our data suggest that the relationship between the genetic counselor and patient may facilitate these broader goals.…”
Section: Discussionmentioning
confidence: 99%
“…Among individuals with PCa, receiving genetic counseling (GC) was the single most signi cant in uence on whether a patient undergoes germline genetic testing (GT) (Borno et al, 2021). GC helps individuals at risk for hereditary cancer syndromes make informed decisions regarding GT and improves patient engagement and satisfaction (Zakas et al, 2019), as well as having impacts for family members if a P/LP gene variant is detected. However, most research into genetic information preferences is focused on females, with only limited studies into the perspectives of white males.…”
Section: Introductionmentioning
confidence: 99%